The Influence of Formula 1 Teams' Content Marketing on Fan Loyalty : A Comparative Analysis of McLaren, Red Bull, and Ferrari. - Evstratenko, Anastasia; Kottika, Efthymia, 1982-; Vinš, Marek; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Content marketing has become the cornerstone of modern marketing strategies. In today's fast-paced digital world, the use of social media has drastically increased, leading to a shift from traditional marketing strategies to digital approaches. This thesis explores the strategic role of content marketing in Formula 1 teams, specifically McLaren, Red Bull, and Ferrari. Through a combination of literature review and qualitative research involving in-depth interviews with fans in the Czech Republic, the study examines how digital content shapes emotional connections, fan engagement, and loyalty. The findings reveal that content marketing is a powerful tool in establishing and maintaining a loyal fan base. The research highlights the importance of storytelling, drivers influence, and audience segmentation in modern sports marketing.
Vedoucí práce: Efthymia Kottika
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses